INAKTIVASI PANAS SPORA BACILLUS CEREUS PADA TAHU - Yudhistira, Bara; Mailia, Reny; Rahayu, Endang S.; Pranoto, Yudi; Rochdyanto, Saiful (Universitas Sebelas Maret (UNS), 2017)
As one of perishable food, tofu is susceptible for microorganisms contamination, an effort is needed to solve the problem. Heat treatment is one of the most common methods used to reduce microorganism population. This research aimed to analyze heat treatment effects of Bacillus cereus reduction in tofu. B. cereus isolate was obtained from soy milk cooking process during tofu production in Sudagaran Yogyakarta. D value measurement as parameter analysis was conducted at 80, 90, 100, 110, 120oC. The results showed that D90 value of B. cereus in tofu product was 29.41 minutes D120 value was 1.69 minute, while Z value was 33.33oC. D and Z value obtained was then used as pasteurization reference to extend shelf life of tofu. Pasteurization temperature of 95oC was based on household conventional boiling temperature, and the process time variations were 0, 10, 30 and 34 minutes. During tofu storage at 100C, analyses conducted were Total Plate Count, spore-forming bacteria, and B. cereus enumeration. Sensory parameter was also evaluated; including flavor, color, surface appearance, mucus presence, and texture. The longest shelf life 20 days was obtained by 34 minutes pasteurization and cool storage.